Vingança: limites e condicionamentos de sua apreensão no processo penal - Gentil, Plínio Antônio Britto (2006)
This search tries to analyse the criminal procedure where something ruled, to where usually are brought categories that, like vengeance, have significant subjective, cultural and religious meaning and, therefore, find great dificullty to be apprehended. The procedure is maken of ruled acts, that include in their interest just that obteined according to their own rules, resulting the stablishment of some kind of procedural truth. These rules, besides the search for a secure decision, makes a reduction on its area of interest, by this way stating conditions to what may be accepted inside the limits of the procedure, very often too strict to apprehend totally, including their contradictions, complexed categories like vengeance, witch illustration is done by the report of a real crime, that, from the beginning to the end, follows the way of the search